2017
DOI: 10.18632/oncotarget.15793
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative adjuvant TACE for patients of hepatocellular carcinoma in AJCC stage I: friend or foe? a propensity score analysis

Abstract: BackgroundAlthough the transcatheter arterial chemoembolization (TACE) was demonstrated to be an alternative treatment of hepatocellular carcinoma with favorable oncological effect, the benefit of postoperative adjuvant TACE was still controversial. The aim of this study was to evaluate the effect of postoperative TACE in hepatocellular carcinoma.ResultsThe 1, 3, and 5–year overall and disease–free survival rates were comparable between Surgery+TACE and Surgery groups. In subgroup analysis, tumor size (≥ 5 cm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…As is known to all, TACE is often the first-line treatment of unresectable or recurrent HCC patients, 24,33,34 but in the recent decade TACE has also been conducted for patients received resection especially in China. 20,35,36 The clinical efficacy of p-TACE was identified by previous studies including one RCT, 13 which was also confirmed by our recent meta-analysis. 15 However, who would be the best candidates of p-TACE remains controversial.…”
Section: Discussionsupporting
confidence: 81%
“…As is known to all, TACE is often the first-line treatment of unresectable or recurrent HCC patients, 24,33,34 but in the recent decade TACE has also been conducted for patients received resection especially in China. 20,35,36 The clinical efficacy of p-TACE was identified by previous studies including one RCT, 13 which was also confirmed by our recent meta-analysis. 15 However, who would be the best candidates of p-TACE remains controversial.…”
Section: Discussionsupporting
confidence: 81%
“…Despite the development in a variety of therapies based on the property of tumor ( e.g ., transcatheter arterial chemoembolization, chemotherapy, molecular targeting therapy, etc .) in recent decades, surgery remains the only curative treatment for patients with primary or metastatic hepatic malignancies[ 2 , 3 ]. Although the remarkable regenerative capacity of the liver permits the extended hepatectomy in clinic, postoperative liver failure caused by small-for-size syndrome (SFSS) represents the most common cause of death after hepatectomy[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because angiogenic factors peak after TACE , some of the micrometastases that have not been eliminated may also be potentially stimulated. Consistently, another study also suggested that TACE is not beneficial for tumors larger than 5 cm . Second, the regimen of adjuvant TACE varied, and questions concerning the exact choice, optimum timing, and preferred cycles remained unanswered.…”
Section: Discussionmentioning
confidence: 94%